Nonlinear vibrations and long-term strength of turbine blades - Breslavsky, D. V.; Morachkovsky, O. K.; Shyriaieva, N. V. (National Technical University "Kharkov Polytechnic Institute", 2010)
The method of a durability estimation of rotating turbomachinery blades at forced flexural-flexural-torsional vibrations is offered. The method is based on the methods of Continuous Damage Mechanics and the accurate strain analysis of the pre-twisted blades at the nonlinear vibrations with moderate displacements. The method to solve the strain analysis problem and turbomachinery blades high-cycle fatigue damage estimation as a result of nonlinear vibrations is presented.